Impact of various heterocyclic π-linkers and their substitution position on the opto-electronic attributes of the A–π–D–π–A type IECIO-4F molecule: a comparative analysis. Issue 32 (20th July 2022) - Akram, Sahar Javaid; Hadia, N. M. A.; Iqbal, Javed; Mehmood, Rana Farhat; Iqbal, Saleem; Shawky, Ahmed M.; Asif, Areeba; Somaily, H. H.; Raheel, Muhammad; Khera, Rasheed Ahmad
Abstract : We have introduced two series of six three-donor molecules, by the substitution of some effective π-linkers on the A–π–D–π–A type reference molecule IECIO-4F (taken as IOR) for efficient organic solar cells. Abstract : To investigate the consequence of different substitution positions of various π-linkers on the photovoltaic properties of an organic solar cell molecule, we have introduced two series of six three-donor molecules, by the substitution of some effective π-linkers on the A–π–D–π–A type reference molecule IECIO-4F (taken as IOR). In series "a" the thienyl or furyl bridge is directly linked between the donor and acceptor moieties, while in series "b" the phenyl ring of the same bridge is working as the direct point of attachment. The frontier molecular orbitals, density of states, transition density matrix, molecular electrostatic potential surfaces, exciton binding energy, excitation energy, wavelength of maximum absorption, open-circuit voltage, fill factor, and some other photovoltaic attributes of the proposed molecules were analyzed through density functional theory (DFT) and its time-dependent (TD) approach; the TD-DFT method. Though both series of newly derived molecules were a step up from the reference molecule in almost all of the studied characteristics, the "a" series (IO1a to IO3a ) seemed to be better due to their desirable properties such as the highest maximum absorption wavelength ( λ max ), open-circuit voltage, and fill factor, along with the lowest excitation and exciton dissociation energy, etc. of its molecules. Also, the studied morphology, optical characteristics, and electronic attributes of this series of proposed molecules signified the fact that the molecules with thienyl or furyl ring working as the direct link between the acceptor and donor molecules showed enhanced charge transfer abilities, and could provide a maximum quantum yield of the solar energy supplied.